The end of alchemy : money, banking and the future of the global economy - King, Mervyn A. (W.W. Norton & Company, 2016)
The former governor of the Bank of England recounts his country's experiences throughout the Great Recession while outlining a blueprint for recovery-era capitalism that is more resilient to modern boom-and-bust cycles.